2017
DOI: 10.3906/sag-1512-93
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between SCGB1D4 gene polymorphisms and susceptibility to adenoid hypertrophy in a pediatric population*

Abstract: Background/aim: Adenoid hypertrophy (AH) is chronic enlargement of the adenoid tissue. The pathophysiology of the disease is unclear. We analyzed SCGB1D4 gene polymorphisms in order to determine the effect of the variants or their genetic combinations on AH. Materials and methods:We genotyped the SCGB1D4 (IIS) gene in 167 participants (95 children with AH and 72 controls) by performing DNA sequencing in blood samples. Results:We genotyped three single nucleotide polymorphisms (SNPs). In the analysis, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This susceptibility to infection may be caused by genetic dispositions. The role of different variations in inflammatory genetic factors, such as polymorphisms of mannose binding lectin (MBL), toll-like receptors (TLRs), secretoglobulins (SCGBs), or IL-10, were analyzed [ 20 , 21 , 22 , 23 ]. Grasso et al found that the MBL2 00 genotype is a prognostic marker of AH in children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This susceptibility to infection may be caused by genetic dispositions. The role of different variations in inflammatory genetic factors, such as polymorphisms of mannose binding lectin (MBL), toll-like receptors (TLRs), secretoglobulins (SCGBs), or IL-10, were analyzed [ 20 , 21 , 22 , 23 ]. Grasso et al found that the MBL2 00 genotype is a prognostic marker of AH in children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Babademez et al stated that TLR4 polymorphisms were associated with an increased risk of AH, but they did not find the same association when they analyzed TLR2 polymorphisms [ 20 ]. In addition, in the work of Özdaş et al, the presence of single nucleotide polymorphisms (SNPs) of secretoglobulins were associated with an increased risk of AH [ 22 ]. Another study demonstrated the role of the IL-10 genotype GG in resistance to hypertrophy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 27 Genetic factors include, among others, polymorphisms in genes coding: SCGB1D4 (IFN-γ stimulated cytokine regulating chemotaxis of immune cells), TLR2 and TLR4 (play a key role in the regulation of the immune system through recognition of molecular patterns commonly found on pathogens (pathogen-associated molecular patterns)). 28 29 …”
Section: Pathogenesis Of Ahmentioning
confidence: 99%
“…Moreover, elevated levels of proinflammatory cytokines such as high-sensitivity C reactive protein, IL-1 and IL-10, interferon-γ (IFN-γ), TNF-α (tumor necrosis factor α) as well as intercellular adhesion molecule-1 in children with AH have been observed 27. Genetic factors include, among others, polymorphisms in genes coding: SCGB1D4 (IFN-γ stimulated cytokine regulating chemotaxis of immune cells), TLR2 and TLR4 (play a key role in the regulation of the immune system through recognition of molecular patterns commonly found on pathogens (pathogen-associated molecular patterns)) 28 29…”
Section: Pathogenesis Of Ahmentioning
confidence: 99%
“…Обнаружение у большинства пациентов с гипертрофией глоточной миндалины вирусов группы герпеса, аденовирусов, человеческого бокавируса подчеркивает их лимфотропность и значимую роль в развитии патологии лимфоглоточного кольца [3,4]. В научной литературе описаны данные, продемонстрировавшие значимость полиморфизма отдельных нуклеотидов генов SCGB1D4 (IIS) и Ugrp2 в повышении риска развития гипертрофии аденоидов у детей и влияние мутации в гене DEFB1 на риск формирования хронического увеличения аденоидной ткани [5,6]. В публикациях отмечено негативное воздействие табачного дыма и неблагоприятных факторов окружаю щей среды на аденоиды у детей, проживающих в крупных городах и промышленных центрах, по сравнению с детьми пригородов и сел.…”
Section: Introductionunclassified